2018
DOI: 10.25002/tji.2018.686
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Th17/Treg balance and Asthma Control Test score by Nigella sativa supplementation in asthmatic children: a new approach to managing asthma

Abstract: Introduction: Th17 and Treg cells have important roles in the development and progression of the allergic diseases, such as asthma. Several studies reported that Nigella sativa could improve chronic airway inflammation, and inhibit airway remodeling by regulating the immune system. To examine the effect of Nigella sativa supplementation on Th17/ Treg cells, and asthma control test score in asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
0
15
0
5
Order By: Relevance
“…In one study, researchers showed that the oils of N. sativa (15–30 mg/kg) significantly decreased Th17 and also increased Treg percentages. In the same way, Th17/Treg ratio was lower in N. sativa treated group compared to the standard treated group [ 138 ]. Supplementation with N. sativa oil in patients with nonalcoholic fatty liver disease (NAFLD) for 8 weeks decreased the level of FBS, lipid profiles (TG, TC, LDL, and VLDL), liver enzymes (AST and ALT), inflammatory marker (hs-CRP, IL-6, and TNF- α ), whereas it increased the HDL-C levels compared to the placebo (paraffin oil) group [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…In one study, researchers showed that the oils of N. sativa (15–30 mg/kg) significantly decreased Th17 and also increased Treg percentages. In the same way, Th17/Treg ratio was lower in N. sativa treated group compared to the standard treated group [ 138 ]. Supplementation with N. sativa oil in patients with nonalcoholic fatty liver disease (NAFLD) for 8 weeks decreased the level of FBS, lipid profiles (TG, TC, LDL, and VLDL), liver enzymes (AST and ALT), inflammatory marker (hs-CRP, IL-6, and TNF- α ), whereas it increased the HDL-C levels compared to the placebo (paraffin oil) group [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, no statement could be made if the change of the intervention group differed significantly from the change in the control group [ 38 ]. Improvements in asthma control as measured via the ACT were reported in three studies using Nigella sativa [ 35 , 39 , 40 ]. Furthermore, an extract of B. serrata gum resin and A. marmelos fruit improved asthma-related quality of life [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overlap between both domains: Five out of six studies from this herb, herbal mixture, or extract cluster showed significant improvements in both asthma-related as well as immunological parameters, compared to the control group [ 34 , 35 , 36 , 37 , 39 , 40 , 41 ]. Nigella sativa ( N = 3) increased ACT score in children with 1.9 points [ 34 , 35 ], and in adults with 1.3, 1.4 [ 40 ] or 2.1 points [ 39 ]. It also increased PEF variability with 8.2 and 5.8 L/min in adults, depending on the dose used [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations